ECHO: A reliable distributed cellular core network for hyper-scale public clouds - Nguyen, Binh; Zhang, Tian; Radunovic, Bozidar; Stutsman, Ryan; Karagiannis, Thomas; Kocur, Jakub; Merwe, Jacobus Van der (Mobicom 2018, 2018)
Economies of scale associated with hyper-scale public cloud platforms offer flexibility and cost-effectiveness, resulting in various services and businesses moving to the cloud. One area with little progress in this direction is cellular core networks. A cellular core network manages the state of cellular clients; it is essentially a large distributed state machine with very different virtualization challenges compared to typical cloud services. In this paper we present a novel cellular core network architecture, called ECHO, particularly suited to public cloud deployments, where the availability guarantees might be an order of magnitude worse compared to existing (redundant) hardware platforms. We present the design and implementation of our approach and evaluate its functionality on a public cloud platform. Analysis shows ECHO promises higher availability than existing telco solutions.